1997
DOI: 10.1021/ja9634942
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Tetrahedral Adducts as Transition-State Analogs and Inhibitors of the Class C β-Lactamase of Enterobacter cloacae P99

Abstract: Previous studies have shown that β-lactamases are inhibited by boronates and phosphonates, both of which form covalent tetrahedral adducts with the active-site serine residue. These have been interpreted, as have similar complexes formed with serine proteinases, as transition-state analog structures. Not all molecules capable of forming such tetrahedral adducts are good inhibitors of serine β-lactamases, however. In this paper, a series of molecules potentially capable of forming anionic tetrahedral adducts at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 75 publications
3
62
1
Order By: Relevance
“…This conformation will be henceforward referred to as Structure A (Scheme 2) and is represented below and shown for 5o in detail in Fig. 2 of the previous paper (36). A structure apparently very similar to A was also attained by 5s, the thiono analog of 5o (Table 2).…”
Section: Methodsmentioning
confidence: 83%
See 3 more Smart Citations
“…This conformation will be henceforward referred to as Structure A (Scheme 2) and is represented below and shown for 5o in detail in Fig. 2 of the previous paper (36). A structure apparently very similar to A was also attained by 5s, the thiono analog of 5o (Table 2).…”
Section: Methodsmentioning
confidence: 83%
“…The final derivative of Although it is probable that longer range interactions might influence the absolute value of calculated interaction energies and conceivably even their relative values, the major aim of the present work was to examine the effects of the local environment and in particular the residues involved in catalysis. Previous results with the P99 ␤-lactamase indicated that long-range interactions did not discriminate between tetrahedral adducts (36). The Builder module of INSIGHT II was also used to construct substrate complexes 15 and 16 along a Bürgi-Dunitz trajectory (42,43).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…compounds containing both boronate and phosphonate groups, can serve as MMP-2 inhibitors, Pergament et al [13]. In addition, X-ray crystallography could show that boronates attach zinc to certain aminopeptidases [14]. This encouraged us to synthesize new organoborane derivatives and test them for possible synergistic * M. S. a and R. R. b are affiliated with the Bloom Center for Pharmacy at the Hebrew University.…”
Section: Introductionmentioning
confidence: 99%